Metabolic Disruptions and Non-Communicable Disease Risks Associated with Long-Term Particulate Matter Exposure in Northern Thailand: An NMR-Based Metabolomics Study - Churdsak Jaikang; Giatgong Konguthaithip; Yutti Amornlertwatana; Narongchai Autsavapromporn; Sirichet Rattanachitthawat; Nitip Liampongsabuddhi; Tawachai Monum (Biomedicines)
Background/Objectives: Particulate matter (PM) is a primary health hazard associated with metabolic pathway disruption. Population characteristics, topography, sources, and PM components contribute to health impacts. Methods: In this study, NMR-based metabolomics was used to evaluate the health impacts of prolonged exposure to PM. Blood samples (n = 197) were collected from healthy volunteers in low- (control; CG) and high-exposure areas (exposure; EG) in Northern Thailand. Non-targeted metabolite analysis was performed using proton nuclear magnetic resonance spectroscopy (1H-NMR). Results: Compared to CG, EG showed significantly increased levels of dopamine, N6-methyladenosine, 3-hydroxyproline, 5-carboxylcytosine, and cytidine (p < 0.05), while biopterin, adenosine, L-Histidine, epinephrine, and norepinephrine were significantly higher in CG (p < 0.05). These metabolic disturbances suggest that chronic exposure to particulate matter (PM) impairs energy and amino acid metabolism while enhancing oxidative stress, potentially contributing to the onset of non-communicable diseases (NCDs) such as cancer and neurodegenerative conditions. Conclusions: This study highlighted the connection between sub-chronic PM2.5 exposure, metabolic disturbances, and an increased risk of non-communicable diseases (NCDs), stressing the critical need for effective PM2.5 reduction strategies in Northern Thailand.